Effect of the Modification of the Start-Up Sequence on the Thermal Stresses for a Microgas Turbine - Oscar Tenango-Pirin; J. C. García; Laura Castro-Gómez; J. A. Rodríguez; F. Sierra; Oscar De Santiago; J. M. Rodríguez-Lelis (International Journal of Rotating Machinery)
Microgas turbines (MGT) are an alternative for small-scale energy production; however, their small size becomes a drawback since it enhances the heat transfer among their components. Moreover, heat transfer drives to temperature gradients which become higher during transient cycles like start-up. The influence of different start-up curves on temperature and thermal stresses of a microgas turbine was investigated. Stationary and rotational blades of the turbine were numerically simulated using CFD and FEM commercial codes. Conjugated heat transfer cases were solved for obtaining heat transfer from fluid toward the blades. Changes of temperature gradients within the blades during the start-ups were calculated under transient state with boundary conditions according to each curve to assess accurate thermal stresses calculations. Results showed that the modification of the start-up curves had an impact on the thermal stresses levels and on the time when highest stresses appeared on each component. Furthermore, zones highly stressed were located near the constraints of blades where thermal strains are restricted. It was also found that the curve that had a warming period at the beginning of the start-up allowed reducing the peaks of stresses making it more feasible and safer for the turbine start-up operation.